2011
DOI: 10.1249/mss.0b013e3182059eda
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen Weeks of Exercise Reduces C-Reactive Protein Levels in Young Women

Abstract: This study demonstrated that a 16-wk aerobic exercise program significantly decreased levels of CRP in young women, especially in those who were obese. There was no evidence that this effect was mediated by changes in perceived stress, percent body fat, or fitness. These findings suggest that adopting an exercise routine early in life may decrease future risk of breast cancer and other chronic diseases in obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 43 publications
6
60
0
9
Order By: Relevance
“…Nevertheless, the relationship among weight loss or exercise, inflammation, and depression or anxiety is only beginning to be established. For example, although a 16-week exercise program was shown to reduce peripheral blood concentrations of CRP in a sample of 319 sedentary women, changes in inflammation, which were especially pronounced in obese exercisers, were not associated with improvements in mood (Arikawa et al, 2011). Nevertheless, it should be noted that these women were not clinically depressed.…”
Section: Reviewmentioning
confidence: 95%
“…Nevertheless, the relationship among weight loss or exercise, inflammation, and depression or anxiety is only beginning to be established. For example, although a 16-week exercise program was shown to reduce peripheral blood concentrations of CRP in a sample of 319 sedentary women, changes in inflammation, which were especially pronounced in obese exercisers, were not associated with improvements in mood (Arikawa et al, 2011). Nevertheless, it should be noted that these women were not clinically depressed.…”
Section: Reviewmentioning
confidence: 95%
“…However, the link between improvement in depressive symptoms and reductions in inflammatory measures has yet to be established. For example, although a 16-week exercise programme was shown to reduce the peripheral blood concentrations of CRP in a sample of 319 sedentary women, changes in inflammation, which were especially pronounced in obese exercisers, were not associated with improvements in mood (Arikawa et al, 2010). Nevertheless, subjects in this and other studies on the effects of exercise on the immune system have not included patients with major depression or patients at risk for depression.…”
Section: Weight Reduction and Dietary Manipulationsmentioning
confidence: 96%
“…In contrast, hsCRP levels increased (65%) in the S1 group. The level of the inflammation marker hsCRP depends on factors such as age, sex, physical activity, nutrition, weight, BMI and smoking [38][39][40][41] and is strongly increased in response to mild infections and inflammations. 2,42 In the present study group, great fluctuations in hsCRP levels were found.…”
Section: Discussionmentioning
confidence: 99%